PENERAPAN GOOD CORPORATE GOVERNANCE PADA PT BPR SUPRA ARTAPERSADA: ANALISIS LAPORAN PENERAPAN TATA KELOLA 2024 - Zahra Yasmin; Gina Sakinah (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the implementation of Good Corporate Governance (GCG) principles at PT BPR Supra Artapersada based on the 2024 governance report using a qualitative approach through secondary data analysis. The TARIF principles (Transparency, Accountability, Responsibility, Independence, and Fairness) serve as the analytical framework to assess the quality of the company’s governance. The findings show that transparency, accountability, and responsibility have been well implemented, as reflected in information disclosure, organizational clarity, and compliance with laws and social programs. However, the company still faces challenges such as family-dominated ownership structures, conflicts of interest in affiliated transactions, and ongoing legal cases. This study concludes that the implementation of GCG at PT BPR Supra Artapersada is relatively good but requires stronger independence and fairness to align governance practices with best practice standards in the microfinance banking sector.